PENERAPAN MANAJEMEN RISIKO OPERASIONAL PADA BANK NAGARI SYARIAH CABANG PEMBANTU PADANG PANJANG - wulan saputri; yola yudia putri yudia putri; wulan saputri wulan wulan (Jurnal Manajemen Bisnis Syariah, 2022)
Today, Islamic banking has a weakness that is the lack of public trust in Islamic banks and prefer to transact in conventional banks. So a new strategy or paradigm is needed to build the image of Islamic banks in order to increase the capacity of banking institutions. New strategies or paradigms in building the image of Islamic banks can be done through the application of banking operational risk management in Islamic state banks.